The association between the Mediterranean Diet and the Prime Diet Quality Score and polycystic ovary syndrome: a case control study - Zeinab Ajorlouie; Paniz Moshkian; Ghazal Baghdadi; Roksaneh Amiri; Fereshteh Biglari; Mehran Rahimlou (BMC Nutrition)
Abstract Introduction Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder affecting women of reproductive age, characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. This study aims to investigate the association between adherence to the Mediterranean Diet (Med-Diet) and the Prime Diet Quality Score (PDQS) and the risk of PCOS. Method This case-control study included 472 women aged 18–45, with 180 PCOS cases and 292 controls. PCOS diagnosis was based on the Rotterdam criteria. Dietary intake was assessed using a validated food frequency questionnaire, and adherence to the Med-Diet and PDQS was calculated. Statistical analyses included logistic regression to examine associations between diet quality and PCOS. Results Higher adherence to both the Med-Diet and PDQS was significantly associated with lower odds of PCOS. Participants in the highest quartile of the Med-Diet score had a 41% reduced risk of PCOS in the crude model (OR = 0.59, 95% CI: 0.48–0.67) and a 32% reduced risk in the fully adjusted model (OR = 0.68, 95% CI: 0.57–0.79), after adjusting for potential confounders, including age, body mass index (BMI), physical activity, and total energy intake. Similarly, those in the highest PDQS quartile showed a 53% reduced risk in the crude model (OR = 0.47, 95% CI: 0.35–0.56) and a 43% reduced risk in the fully adjusted model (OR = 0.57, 95% CI: 0.44–0.68), accounting for the same confounders. Conclusion The findings suggest that higher adherence to the Med-Diet and PDQS is associated with a reduced risk of developing PCOS. Further research is warranted to explore the underlying biological mechanisms and to establish causality through prospective cohort studies and randomized controlled trials.